Gasdermin D deletion prevents liver injury and exacerbates extrahepatic damage in a murine model of alcohol-induced ACLF - Yuan Zhuang; Gyongyi Szabo; Martí Ortega-Ribera; Veronika Brezani; Radhika S Joshi; Zsuzsanna Zsengeller; Prashanth Thevkar Nagesh; Aditi Datta (eGastroenterology)
Background Gasdermin D (GSDM-D), a key executor of pyroptosis, is increased in various liver diseases and contributes to disease progression. Alcohol induces inflammasome activation and cell death, which are both linked to GSDM-D activation. However, its role in alcohol-induced acute-on-chronic liver failure (ACLF) remains unclear.Methods ACLF was induced in GSDM-D-deficient or wild-type (WT) mice by 28-day bile duct ligation surgery plus a single 5 g/kg alcohol binge leading to acute decompensation. Nine hours after the alcohol binge, blood, liver, kidney and cerebellum specimens were collected for analysis.Results Active GSDM-D was significantly increased in humans and mice ACLF livers compared with both healthy controls and cirrhotic livers. GSDM-D-deficient mice with ACLF showed decreased inflammation, neutrophil infiltration and fibrosis in the liver, together with a reduction in pyroptotic, apoptotic and necroptotic death, compared with WT ACLF mice. Notably, GSDM-D-deficient mice also showed decreased liver regeneration and hepatocyte function. This was associated with an increase in senescence and expression of stem-like/cholangiocyte markers in the liver. Interestingly, in the kidney, GSDM-D-deficient mice showed an increase in histopathological damage score, decreased function and increased expression of necroptosis-related genes. In the cerebellum, GSDM-D deficiency increased the expression of neuroinflammation markers, astrocyte activation and apoptosis-related genes.Conclusion Our data indicate that GSDM-D deficiency has organ-specific effects in ACLF. While it reduces inflammation, neutrophil activation, cell death and fibrosis in the liver, GSDM-D deficiency impairs the synthetic function and increases senescence in hepatocytes. GSDM-D deficiency also increases kidney injury and neuroinflammation in ACLF.